A Scoping Review of the Effect of Content Marketing on Online Consumer Behavior. (April 2022) - du Plessis, Charmaine
Notwithstanding the body of research on the characteristics and benefits of content marketing as a digital marketing strategy, evidence of how online consumer behavior is affected by digital brand content remains inconclusive. The current state results from the scattered and fragmented literature about content marketing which impedes a full understanding of scientific results that confirm the effect of content marketing activities on online consumer behavior. The purpose of this scoping review was therefore to provide a broad synopsis of pertinent studies in a structured and comprehensive way over 12 years. The scoping review upheld the five-stage framework of Arksey and O'Malley and was guided by the principles of PRISMA-ScR and the JBI Methodological guidelines. In doing so, the findings from 32 studies conducted in 21 different countries were analyzed and suggestions made for future research. The results not only synthesize existing empirical evidence of the causal linkage between content marketing and online consumer behavior but also identify some knowledge gaps in the literature to guide future studies.